Allogeneic Hematopoietic Stem Cell Transplant Offer Good Outcomes in Pediatric Aplastic Anemia: Experience From Developing World. Issue 5 (28th July 2021) - Sachdev, Mansi; Bansal, Minakshi; Chakraborty, Sohini; Jain, Sachin; Bhargava, Rahul; Dua, Vikas
Abstract : Between 2014 and 2020, 31 patients with severe aplastic anemia (SAA) underwent full match allogeneic hematopoietic stem cell transplantation at our center. Of the 31 patients with SAA, 19 had acquired aplastic anemia, 2 had Diamond Blackfan anemia and 10 had Fanconi anemia. Donors were either matched sibling (n=29), related donors (n=2), or unrelated donors (n=3). Peripheral blood stem cells were the graft source in all the cases except 1. Fludarabine-based reduced intensity conditioning was used in all except for patients with a diagnosis of Diamond Blackfan anemia. All patients except 1 achieved hematologic recovery in the form of neutrophil engraftment at 13 days (range, 9 to 17), whereas platelet engraftment occurred at 14 days (range, 10 to 18). Graft versus host disease (GvHD) prophylaxis consisted of cyclosporine and methotrexate ±antithymocyte globulin (horse/rabbit). Acute GvHD developed in 12.9% patients, whereas no patients developed chronic GvHD till the time of last follow-up. The 2-year overall survival for the entire cohort was 93.21±4.6%. In patients with SAA, allogeneic stem cell transplant using fludarabine-based conditioning regimens are very well tolerated and have excellent outcomes in a full match setting.